Seizure severity and health-related quality of life of adult Nigerian patients with epilepsy - Adebayo, P. B.; Akinyemi, R. O.; Ogun, S. A.; Ogunniyi, A. (Acta neurologica Scandinavica, 2014)
Objectives There is paucity of information about the association of seizure severity and quality of life in people with epilepsy (PWE) in sub‐Saharan Africa. We evaluated the relationship of seizure severity to health‐related quality of life of patients with epilepsy being followed up in an outpatient neurology clinic in southwestern Nigeria. Materials and methods Eighty‐eight consecutive patients with epilepsy who met the recruitment criteria completed the study questionnaire in company of an eyewitness. The study questionnaire comprised of the National Hospital Seizure Severity Scale (NHS3), the Quality of Life Inventory in Epilepsy (QOLIE‐31), and the Beck's Depression Inventory‐II (BDI‐II). Results We found a minute association between seizure severity and QOLIE‐31 total score (r = −0.262, P = 0.014). Increased seizure severity predicted a worse QOLIE‐31 seizure worry (R2 = 0.311, β = −0.289; P = 0.003). Of the seven seizure severity items, generalization of seizures and presence of falls were items that predicted a worse QOLIE‐31 seizure worry score and time to recover predicted a worse QOLIE‐31 total score. Conclusions Reducing seizure severity may be an alternate endpoint in epilepsy care in Nigeria (particularly difficult to control seizures) because of its practical clinical relevance in view of the fact that state‐of‐the‐art epilepsy care is still farfetched.